Hemolytic-Uremic Encephalopathy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1992)
Twenty-seven children, ages 6 months - 13 years, with encephalopathy complicating hemolytic-uremic syndrome are reported from The University of British Columbia, Vancouver, Canada.